Tolerância de porta-enxertos de videira ao encharcamento - Mendonça, Luciana Freitas de Medeiros (2012)
To evaluate grapevine rootstock cultivars and its tolerance to waterlogging, an experiment was conducted in UFERSA in 2010. The experimental design was in a randomized blocks in 4 x 6 factorial. Six rootstocks (Harmony, 1103 Paulsen, Riparia of Traviú, IAC 572 'Jales', IAC 571-6 'Jundiaí' and IAC 766 'Campinas') and four periods of waterlogging (0, 4, 7 and 14 days) were tested in four replications. Cuttings were rooted in polyethylene bags containing sand and Plantmax ® (3:1 v / v) as substrate. At the time of application of treatments, bags were placed in polystyrene boxes containing water up plants collar, with a block in each box. The application was in reversed order of time. The fourteen-day waterlogging period treatment was placed in box in the first day, seven days after that the seven-days, three days after that the four-days one. Four days later, all the boxes were emptied, completing the cycle. At the end of the waterlogging, evaluation was made for maximum leaf water potential, photosynthesis measurements, transpiration, stomatal conductance, intracellular CO2 concentration, leaf temperature were done; water use efficiency and carboxylation efficiency were also measured. Using relative humidity and temperature data, the values of water vapor pressure deficit were obtained. For the determination of chlorophyll it was used a portable chlorophyll meter. Plant growth variables were number of leaves, number of branches, branch length, branch diameter and length of the root system. In addition, plants were separated and dryed in an oven at 65 ° C until constant weight for further evaluation of the dry mass of leaves, shoots, cuttings, root mass and total dry mass. Waterlogging affected negatively the growth and physiology traits of rootstock genotypes studied. Genotypes and waterlogging time were important factors in determining the severity of injuries caused by waterlogging. Waterlogging time affected the growth of branches from the third day, just as affected stomatal conductance and photosynthesis from day 2, influence that increased with increasing stress. Cultivar Paulsen 1103 was more sensitive to waterlogging, with sudden drops in test values as the soaking time increased, while values of cultivar the Ripária of Traviú cultivar remained more constant during the waterlogging time, fact that can be considered a sign of tolerance to this type of environmental stress